Organ-Protective Effect of Red Ginger Extracts in Male Mice Induced by Paraquat - Kamiliah Tsany; Sutyarso Sutyarso; M. Kanedi; Hendri Busman (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
Paraquat is a toxic compound that disrupts biochemical processes in the body, cell death, and multi-organ failure. The liver and lung are the target organ of paraquat toxicity. The body needs antioxidants to counteract free radicals. Red ginger (Zingiber officinale Roxb. Var rubrum) is a spice that contains antioxidants. This study was conducted to determine the effect of ethanol extract of red ginger (Zingiber officinale Roxb. Var rubrum) on liver and lung histology male mice induced by paraquat. The research used completely randomized design and use of 6 treatment groups, i.e. control group (given distilled water and standard feed), PQ group (induced by paraquat 20 mg/kg per BW), group P1 (given paraquat and ethanol extracts of red ginger 200 mg/kg per BW), group P2 (given paraquat and ethanol extract of red ginger 400 mg/kg per BW), group P3 (given paraquat and ethanol extract of red ginger 600 mg/kg per BW), group P4 (given ethanol extract of red ginger extract 600 mg/kg per BW). The data obtained will be tested using One Way ANOVA and continued by Least Significant Difference (LSD) with a 95% confidence level. The results showed ethanol extract of red ginger effective against liver and lung histology male mice induced by paraquat. The results also showed ethanol extract of red ginger with a dose of 400 mg/kg per BW is effective in protecting the liver and lung from damage caused induced by paraquat.